An evaluation of the gold share market on the JSE - Bradfield, David John (Department of Statistical Sciences, 2023)
Gold has traditionally been a highly· prized metal, .stored for value and used in the manufacture of ornaments and jewellery; its use dates as far back as the Ancient Egyptians. Since August 1971, however when the dollar/gold convertibility was officially terminated, the price of gold bullion has become very volatile, but has also increased so rapidly that the attractive profits that were attainable in the gold bullion and gold share markets attracted many speculators. The volatile gold price over this period, however, has also been the cause of many lost fortunes. The following quotation extracted from the Supplement to the Financial Mail (May 30, 1980) emphasizes this point with--some cynicism.